2015
DOI: 10.3390/su70810036
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Industrial Parks Development and Integrated Management Challenges: Findings from Italy

Abstract: Abstract:The evolution of Eco Industrial Parks (EIPs) in Italy is a development opportunity for many territories and companies. Starting from the initial experiences in the 1980s, the Eco Industrial Parks model has spread throughout many of the central and northern regions of the country. The key element of Italian Eco Industrial Parks is the management body, an entity provided by national legislation to manage and coordinate companies and to develop more environmentally sustainable production practices. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…This is consistent with recent findings showing that, for successful development and operation of eco-innovation parks, the success factor with the highest occurrence is related to the organizational and institutional setup of the parks and more specifically to the presence of an effective coordination body [13], also referred to as a management body [62]. A study of EIPs in Italy found that the main activities carried out by EIP management bodies were managing the environmental services for the companies and managing the development and promotion of the EIP through communication and dissemination initiatives [62]. One of the main roles of the management body was found to be the consultation with local stakeholders [62].…”
Section: Environmental Management Organizationsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with recent findings showing that, for successful development and operation of eco-innovation parks, the success factor with the highest occurrence is related to the organizational and institutional setup of the parks and more specifically to the presence of an effective coordination body [13], also referred to as a management body [62]. A study of EIPs in Italy found that the main activities carried out by EIP management bodies were managing the environmental services for the companies and managing the development and promotion of the EIP through communication and dissemination initiatives [62]. One of the main roles of the management body was found to be the consultation with local stakeholders [62].…”
Section: Environmental Management Organizationsupporting
confidence: 92%
“…A study of EIPs in Italy found that the main activities carried out by EIP management bodies were managing the environmental services for the companies and managing the development and promotion of the EIP through communication and dissemination initiatives [62]. One of the main roles of the management body was found to be the consultation with local stakeholders [62]. In practice though, EIP development with a comprehensive environmental management system at the park level is a relatively new concept [32].…”
Section: Environmental Management Organizationmentioning
confidence: 99%
“…The landscape provided by the European Union, which has been encouraging Member States to increase the environmental performance of its territories, has nurtured the Italian context to boost the transition of industrial production systems into more sustainable and eco-compatible spaces. Along these lines, the Ecologically Equipped Productive Areas (EEPAs) was the first initiative introduced by the Italian Government in 1998 (Tessitore, et al, 2015), and the first concrete attempt in Italy to search for a new industrial production model through the application of the IE principles on the EIP development model (Daddi, et al, 2015).…”
Section: The Italian Contextmentioning
confidence: 99%
“…In Italy, Tessitore et al (2015) studied the evolution of eco-industrial parks and stated that it is a development opportunity for many territories and companies where the key element of Italian eco-industrial parks is the management body, an entity provided by national legislation to manage and coordinate companies and to develop more environmentally sustainable production practices. The study introduced an important environmental management experience implemented in Italy.…”
Section: Introductionmentioning
confidence: 99%